Heterozygous mutation of Drosophila Opa1 causes the development of multiple organ abnormalities in an age-dependent and organ-specific manner. - Shahrestani, P.; Leung, H.T.; Le, P.K.; Pak, W.L.; Tse, S.; Ocorr, K.; Huang, T. (PLoS ONE, 2009)
Optic Atrophy 1 (OPA1) is a ubiquitously expressed dynamin-like GTPase in the inner mitochondrial membrane. It plays important roles in mitochondrial fusion, apoptosis, reactive oxygen species (ROS) and ATP production. Mutations of OPA1 result in autosomal dominant optic atrophy (DOA). The molecular mechanisms by which link OPA1 mutations and DOA are not fully understood. Recently, we created a Drosophila model to study the pathogenesis of optic atrophy. Heterozygous mutation of Drosophila OPA1 (dOpa1) by P-element insertion results in no obvious morphological abnormalities, whereas homozygous mutation is embryonic lethal. In eye-specific somatic clones, homozygous mutation of dOpa1 causes rough (mispatterning) and glossy (decreased lens deposition) eye phenotypes in adult Drosophila. In humans, heterozygous mutations in OPA1 have been associated with mitochondrial dysfunction, which is predicted to affect multiple organs. In this study, we demonstrated that heterozygous dOpa1 mutation perturbs the visual function and an ERG profile of the Drosophila compound eye. We independently showed that antioxidants delayed the onset of mutant phenotypes in ERG and improved larval vision function in phototaxis assay. Furthermore, heterozygous dOpa1 mutation also caused decreased heart rate, increased heart arrhythmia, and poor tolerance to stress induced by electrical pacing. However, antioxidants had no effects on the dysfunctional heart of heterozygous dOpa1 mutants. Under stress, heterozygous dOpa1 mutations caused reduced escape response, suggesting abnormal function of the skeletal muscles. Our results suggest that heterozygous mutation of dOpa1 shows organ-specific pathogenesis and is associated with multiple organ abnormalities in an age-dependent and organ-specific manner.